A new species of Tactusa Fibiger, 2010 from Autonomous Region Xizang, China. (Lepidoptera, Erebidae, Hypenodinae). Taxonomic study of Micronoctuini. Contribution II - Han, Hui Lin; Kononenko, Vladimir S. (Zootaxa, 2021)
A new species of the genus Tactusa Fibiger, 2010, T. motuoensis sp. n. is described from the Autonomous Region Xizang (Tibet), China. Key to the species of the genus Tactusa in China, based on the male genitalia is presented. Eight species of Tactusa referred for China.